An efficient simulation method for the first excursion problem of linear structures subjected to stochastic wind loads. (1st April 2016) - Wang, Jia; Katafygiotis, Lambros S.; Feng, Zhouquan
Highlights: First excursion problem of linear structures subjected to wind loads is considered. The geometry of the failure domain of the reliability problem is explored. An enhanced efficient simulation method is developed for the concerned problem. Abstract: In this paper the first excursion problem of linear structures subjected to stochastic wind loads is considered. The geometry of the corresponding failure domain is further explored, with the finding that rotational relationship exists for the quadratic elementary failure domains comprising the overall failure domain. Besides, procedures using the gradient projection method are developed for obtaining the design point of the quadratic elementary failure domain, which can be used to modify the previously developed simulation method. An illustrative example shows the accuracy and the enhanced efficiency of the modified simulation method, compared with its original version.